Association of triglyceride glucose-body mass index with non-small cell lung cancer risk: A case-control study on Chinese adults - Wang, Feifei; He, Ting; Wang, Guoliang; Han, Tuo; Yao, Zhongqiang (Frontiers in Nutrition, 2022)
Background and objectives: Insulin resistance (IR) is closely related to non-small-cell lung cancer (NSCLC) risk. Recently, the triglyceride glucose-body mass index (TyG-BMI) has been recognized as one of simple indexes of insulin resistance (IR) . However, there is limited data about the relationship between TyG-BMI and NSCLC. Here, we investigated the association of TyG-BMI with NSCLC risk in Chinese adults. Methods: This study consisted of 477 NSCLC cases and 954 healthy subjects. All participants were enrolled from 3201 Hospital Affiliated to Medical Department of Xi'an Jiaotong University. The TyG-BMI was calculated based on the values of fasting blood glucose, triglyceride and BMI. The association of TyG-BMI with NSCLC risk was estimated using logistic regression analysis. Results: The mean value of TyG-BMI was statistically increased in patients with NSCLC compared to the control group (201.11±28.18 vs 174.00±23.78, P<0.01). There was a significant positive association between TyG-BMI and NSCLC (OR=1.014, 95%CI 1.007-1.021, P<0.001), after controlling for confounding factors. Moreover, the prevalence of NSCLC was significant elevated in participants in the high TyG-BMI tertiles than those in the intermediate and low TyG-BMI tertiles ( 60.46% vs 12.61% vs 26.83% , P<0.01). Importantly, TyG-BMI achieved significant diagnostic accuracy for NSCLC, with the AUC (area under the curve) of 0.769 and a cut off value of 184.87. Conclusions: The findings suggest that TyG-BMI is a useful tool for assessing NSCLC risk. Thus, it is essential to follow-up the high TyG-BMI, and lifestyle modification is needed to prevent NSCLC in people with high TyG-BMI.